Evaluation of neural response telemetry (NRT™) with focus on long-term rate adaptation over a wide range of stimulation rates. (May 2014) - Huarte, Alicia; Ramos, Angel; Morera, Constantino; Garcia-Ibáñez, Luis; Battmer, Rolf; Dillier, Norbert; Wesarg, Thomas; Müller-Deile, Joachim; Hey, Mattias; Offeciers, Erwin; von Wallenberg, Ernst; Coudert, Chrystelle; et al.
Abstract : Custom Sound EP™ (CSEP) is an advanced flexible software tool dedicated to recording of electrically evoked compound action potentials (ECAPs) in Nucleus ® recipients using Neural Response Telemetry™ (NRT™). European multi-centre studies of the Freedom™ cochlear implant system confirmed that CSEP offers tools to effectively record ECAP thresholds, amplitude growth functions, recovery functions, spread of excitation functions, and rate adaptation functions and an automated algorithm (AutoNRT™) to measure threshold profiles. This paper reports on rate adaptation measurements. Rate adaptation of ECAP amplitudes can successfully be measured up to rates of 495 pulses per second (pps) by repeating conventional ECAP measurements and over a wide range of rates up to 8000 pps using the masked response extraction technique. Rate adaptation did not show a predictable relationship with speech perception and coding strategy channel rate preference. The masked response extraction method offers opportunities to study long-term rate adaptation with well-defined and controlled stimulation paradigms.